(untitled) (Jurnal Pertanian Terpadu, 2025)
This study aims to identify and group the types of insects found in three local sorghum genotypes of East Sumba, namely WH Mitting Nggangga, WH Rara Kadita, and WH Mitting Tadda. The study was conducted at the Sains Technopark land, Satya Wacana Christian University, from June to November 2024. The method used was exploratory by systematically installing yellow traps to observe the population and role of insects. The results showed that the orders Hemiptera and Diptera were the most dominant, with the genera Bemisia sp. and Musca sp. as the main pests. The highest number of insects was found in the WH Mitting Tadda genotype (1257 individuals), and the lowest in WH Mitting Nggangga (1096 individuals). The diversity index (H’) was in the moderate category, between 1.52–1.67, and the dominance index was also moderate, between 0.26–0.30. Predatory and pollinating insects were found in smaller numbers than pests. These results indicate that the balance of the ecosystem in cultivated land is still quite stable, but requires attention to pest management and conservation of natural enemies so that sorghum productivity remains optimal. Keywords: Sorghum agroecosystem, Dominant pests, Diversity index, Natural enemies, Insect trap